The Impact of Investment Decisions, Funding Decisions, and Dividend Policy on The Valuation of Manufacturing Companies Listed on The IDX - Purwita, Citra (Strata Business Review, 2024)
This study examines the impact of investment decisions, funding deThis study examines the effects of investment decisions, funding decisions, and dividend policies on the value of manufacturing businesses listed on the IDX stock exchange. This study employs a quantitative research methodology with a descriptive approach. The research sample consisted of 127 manufacturing businesses listed on the Indonesia Stock Exchange between 2017 and 2020. The research employed the purposive sampling approach as its sampling strategy. The data included in this study is derived from secondary sources. This research used the SPSS Statistics version 26 program for data analysis, with multiple regression analysis as the chosen analytical tool. The research findings indicate that investment decisions do not have any impact on the value of the firm, however funding decisions and dividend policies have a positive influence on the company's value.